The Effect of Net Profit Margin (NPM), Price to Book Value (PBV), Current Ratio (CR), and Total Asset TurnOver (TATO) Influence on Earning Per Share (EPS) in Real Estate and Property Companies Listed on the IDX 2013-2018 - Lailatul Muflihah; Sriyono Sriyono (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of the Net Profit Margin, Price to Book Value, Current Ratio, and Total Asset TurnOver to Earning Per Share in Real Estate and Property Componies Listed on the Stock Exchange in 2013–2018. This research is a quantitative reseach method with an associative research approach or relationship. The results of this study indicate that Net Profit Margin (X1), Price to Book Value (X2), Current Ratio (X3), and Total Asset TurnOver (X4) simultaneously influence in determining the Earning Per Share variable. While the variable Net Profit Margin (X1) and Total Asset TurnOver (X4) does not have a significant effect on Earning Per Share because the lower this variable, the better it is to measure is long-term debt o the company, and asset turnover as measured by sales volume will it is very important for creditors and shareholders, and even more important for company management to see how efficient the conditions of using their assets are in the company.